2010
DOI: 10.1007/s10695-009-9305-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on muscle lactate metabolic recovery in sea bass (Dicentrarchus labrax, L.) juveniles exposed to exhaustive exercise

Abstract: Muscle lactate metabolic recovery in sea bass juveniles was studied in respect to the water temperature. The fish used in this study were cultured with the semi-extensive mesocosm method, and the water temperatures were 15 and 20 degrees C. Fish were led to exhaustion by exercising in a swimming channel, and the muscle lactate levels were measured seven times before and after exercise. The results showed that muscle lactate concentration rises during exercise until it reaches a maximum (exhaustion point), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
3
6
0
1
Order By: Relevance
“…Fish were euthanized with ethyleneglycolmonophenylether (Merck, 0.2-0.5 ml l -1 ) and muscle tissue of the haemal part of the body was removed and stored at -80 • C for further analysis (McClelland et al 2006). The LactPap kit (61.192, bioMérieux, France) was used for lactate concentration measurement according to the method described by Barnett & Pankhurst (1998) and validated for zebrafish by Sfakianakis & Kentouri (2010). Data were afterwards analyzed by means of non-parametric Kruskal-Wallis and Mann-Whitney U tests, since the assumptions for normality and homoscedasticity were not met.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish were euthanized with ethyleneglycolmonophenylether (Merck, 0.2-0.5 ml l -1 ) and muscle tissue of the haemal part of the body was removed and stored at -80 • C for further analysis (McClelland et al 2006). The LactPap kit (61.192, bioMérieux, France) was used for lactate concentration measurement according to the method described by Barnett & Pankhurst (1998) and validated for zebrafish by Sfakianakis & Kentouri (2010). Data were afterwards analyzed by means of non-parametric Kruskal-Wallis and Mann-Whitney U tests, since the assumptions for normality and homoscedasticity were not met.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature can affect time of hatching, growth, metabolism (Herzig & Winkler 1986), muscle ontogeny and development (Johnston 1993), swimming performance (Koumoundouros et al 2002a;Sfakianakis et al 2011a), external morphology and meristic characters (Turan 2004;Sfakianakis et al 2011b), osteological development and appearance of skeletal deformities (Koumoundouros et al 2001;Sfakianakis et al 2004), sex determination (Koumoundouros et al 2002b) and the overall survival of fish (Lein et al 1997). Exercise-associated fish metabolism is also among the characteristics that are significantly affected by temperature (Sfakianakis & Kentouri 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of organisms to stress may also be influenced by environmental conditions, including temperature (Wieser et al, 1986; Lankford et al, 2003; Davis, 2004). In the case of fish, studies have indicated that high temperatures can lead to a more pronounced hormonal (Barton and Schreck, 1987; Jaxion-Harm and Ladich, 2014) or metabolic response (Kieffer et al, 1994; Sfakianakis and Kentouri, 2010). Cold temperatures, on the other hand, have often been found to dampen the magnitude of this response (Van Ham et al, 2003; Davis, 2004; Guderley, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although we do not report mortality in the current study, it is likely that deformed embryos would not survive. In fish, the appearance of morpho-anatomical deformities can be associated with temperature (Wang and Tsai, 2000;Koumoundouros et al, 2009;Sfakianakis and Kentouri, 2010). There is a lack of published data on the influence of temperature on fish body shape and especially on specimens reared under laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%